2018
DOI: 10.1055/s-0038-1636534
|View full text |Cite
|
Sign up to set email alerts
|

Incident Risk Factors and Major Bleeding in Patients with Atrial Fibrillation Treated with Oral Anticoagulants: A Comparison of Baseline, Follow-up and Delta HAS-BLED Scores with an Approach Focused on Modifiable Bleeding Risk Factors

Abstract: In this 'real-world' nationwide AF cohort, follow-up HAS-BLED or 'delta HAS-BLED score' was more predictive of major bleeding compared with baseline HAS-BLED or the simple determination of 'modifiable bleeding risk factors'. Bleeding risk in AF is a dynamic process and use of the HAS-BLED score should be to 'flag up' patients potentially at risk for more regular review and follow-up, and to address the modifiable bleeding risk factors during follow-up visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 18 publications
0
117
0
4
Order By: Relevance
“…42 Moreover, the follow-up HAS-BLED has more predictive value for major bleeding as compared with baseline HAS-BLED because bleeding risk in AF patients is a dynamic process. 43 Studies have already illustrated that bleeding risk assessment based on modifiable risk factors alone (as proposed by the ESC guidelines) is an inferior strategy compared to a formal bleeding risk score like the HAS-BLED score. 44,45 The ABC-bleeding tool is a recently proposed assessment tool, which adds GDF-15, Troponin T, and hemoglobin biological indicators to predict the risk of major bleeding events within 1 or 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, the follow-up HAS-BLED has more predictive value for major bleeding as compared with baseline HAS-BLED because bleeding risk in AF patients is a dynamic process. 43 Studies have already illustrated that bleeding risk assessment based on modifiable risk factors alone (as proposed by the ESC guidelines) is an inferior strategy compared to a formal bleeding risk score like the HAS-BLED score. 44,45 The ABC-bleeding tool is a recently proposed assessment tool, which adds GDF-15, Troponin T, and hemoglobin biological indicators to predict the risk of major bleeding events within 1 or 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline evaluation and management of bleeding risk, as well as the routine reevaluation during the clinical follow‐up, are pivotal for patients with AF to minimize occurring bleeding events 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…Finally, studies have often correlated stroke occurrences during long periods of follow-up to risk factors measured at baseline, and risk changes with increasing age and incident risk factors. Indeed, recent attention has been directed toward the dynamic nature of risk profiles in AF patients (176)(177)(178). Chao et al found the majority of patients with AF (89.4%) developed ≥1 new risk factor(s) prior to presenting with an ischemic stroke (178).…”
Section: Limitations Of Risk Scoresmentioning
confidence: 99%